Redefining Roles In Organizational Change: An Integrated Framework Based On The ENGAGE Star Change Model - Tourista, Meiko; Sutanto, Eddi; Azwir, Akbar (Journal of Industrial Engineering & Management Research, 2025)
Organizational transformation hinges on the effectiveness of roles executing both technical delivery and human adoption, yet current change methodologies lack a unified framework for role integration. This paper introduces the ENGAGE Star Pillars framework, a model designed to establish role governance by explicitly mapping key change functions to the six stages of the ENGAGE adoption cycle (Enlighten to Embed).The framework addresses critical inconsistencies found in existing literature—which often marginalize the Change Agent (e.g., Prosci) or omit Project and Change Manager roles (e.g., Kotter)—by unifying four essential functions under distinct, measurable pillars: Project Management (CCC framework), Sponsorship (CHAMPION), Change Management (EEE framework), and the Change Agent (BEACON). This architecture rests on the foundation of Leadership and Strategy and culminates in measurable Change Success.This study aims to clarify the specific actions and capabilities required of core roles across the entire adoption lifecycle, based on the ENGAGE Star Change Model. The ENGAGE Star Pillars framework serves as a practical, integrated governance model that eliminates accountability ambiguity, significantly accelerates adoption by coordinating the technical and people-centric efforts, and ultimately ensures the realization of strategic outcomes.